A pathogenic progranulin mutation and C9orf72 repeat expansion in a family with frontotemporal dementia. Issue 4 (June 2014) - Lashley, Tammaryn; Rohrer, Jonathan D.; Mahoney, Colin; Gordon, Elizabeth; Beck, Jon; Mead, Simon; Warren, Jason; Rossor, Martin; Revesz, Tamas
<x xml:space="preserve">Abstract</x> Aims Frontotemporal lobar degeneration (FTLD) is a progressive neurodegenerative disease and is the second most common form of young onset dementia after Alzheimer's disease (AD). An autosomal dominant pattern of inheritance is present in around 25–50% of FTLD cases indicating a strong genetic component. Major pathogenic mutations of FTLD have been demonstrated independently in the progranulin (GRN) gene and the C9orf72 hexanucleotide expansion repeat. In this study we present a family that have been identified as carrying both a GRN Cys31fs mutation and the C9orf72 hexanucleotide expansion repeat. Methods In the present study we describe the clinical and genetic details of family members and pathological features of two family members that have come to post‐mortem. Results The mean age at disease onset was 57 years (48–61 years) and mean duration 4 years (2–7 years). The most common presenting syndrome was behavioural variant frontotemporal dementia. Brain imaging from available cases showed a symmetrical pattern of atrophy particularly affecting the frontal and temporal lobes. Pathologically two cases were classified as FTLD‐TDP type A with TDP‐43 positive inclusions, with additional p62‐positive 'star‐like' inclusions found in the hippocampal formation and cerebellum. Conclusions The type and distribution of the pathological lesions in these two cases were in keeping with FTLD cases carrying only the C9orf72 hexanucleotide repeat. However the driving force of the pathological process may be either pathogenic mutation or a combination of both converging on a singular mechanism.